87 Outcomes of PCI Versus Medical Therapy in a Surgical Turndown Cohort from a Single Centre. (31st May 2014) - Danson, Edward; Byrne, Jonathan; Groves, Chris; Sapontis, James; Dworakowski, Rafal; MacCarthy, Philip; Shah, Ajay; Hill, Jonathan
Abstract : Background: There is limited data describing outcomes in patients undergoing percutaneous coronary intervention (PCI) or medical therapy who have been turned down for surgical revascularisation (CABG) on the basis of prohibitive risk. The independent predictors of morbidity and mortality; and role of clinical or anatomical scoring systems in this patient group are incompletely understood. Methods: We analysed cardiovascular outcomes (major adverse clinical event rate, MACE: death; myocardial infarction, MI; target vessel revascularisation, TVR; and stroke) in a retrospective cohort of patients turned down for elective CABG who were treated with PCI or medical therapy in a single centre in 2012. Patients were subdivided into SYNTAX tertiles for comparing outcomes. Clinical data were gathered (age, sex, hypertension, smoking, diabetes, hyperlipidaemia, renal dysfunction, LV dysfunction, COPD, stroke, cognitive impairment, reduced mobility, peripheral vascular disease, neoplaisia, 3 vessel disease, left main disease, chronic occlusion, valve disease, sinus rhythm, permenant pacing, Euroscore II and SYNTAX scores) and independent predictors of 1 year and 30 day MACE and mortality were identified using multivariate stepwise logistic regression analysis. Results: There were a total of 77 patients with a mean(±standard error) age of 74 ± 1.2 years. The total 1 year MACE rate was 22 ± 1.9% (14% death, 8% MI, 1% TVR, 0% stroke) and 30 day MACE rate was 6 ± 1.1% (5% death, 1% MI). Within the low SYNTAX tertile (0–22), the MACE rate was significantly higher in the medically treated group (33 ± 2%) compared to the PCI group (6 ± 1%, Relative Risk Reduction 82%; P < 0.05 Chi-squared test). There was no difference between MACE rates in the intermediate (23–33; Medical: 15 ± 3% vs. PCI: 24 ± 4%) or high SYNTAX groups (>33; Medical: 27 ± 4% vs. PCI: 60 ± 12%). Independent predictors of MACE and mortality were SYNTAX score, the presence of 3 vessel coronary disease and reduced left ventricular function. Surprisingly neither Euroscore II (mean 4.89 ± 0.59%) nor the presence of neoplasia were statistically associated with MACE or mortality on either univariate or multivariate analyses. Conclusion: This data supports the use of SYNTAX scoring as a predictor of outcome in patients turned down for CABG in a single-centre setting.Within our cohort of surgically turned down patients, those within the low SYNTAX tertile appeared to be the only group that achieve a clear benefit of PCI over medical therapy.